Comparison of Different IOL Types in the Flanged IOL Fixation Technique - Yusaku Miura; Yosuke Harada; Yoshiaki Kiuchi (Journal of Ophthalmology)
Purpose. To compare short-term clinical outcomes between two different intraocular lens (IOL) types in the flanged IOL fixation technique. Methods. This study was a retrospective case series and included the patients who underwent flanged IOL fixation between June 2017 and July 2018 at the Hiroshima University Hospital. Two different 3-piece IOLs (NX-70 and PN6A) were used. Recipients of NX-70 and PN6A IOLs were classed into groups 1 (15 eyes) and 2 (25 eyes), respectively. Patient characteristics, surgical results, and postoperative complications were analyzed. We excluded patients with a postoperative follow-up of <1 month. Results. The mean follow-up period was 13.3 ± 11.7 weeks. The postoperative best corrected visual acuity, in logarithm of the minimum angle of resolution (logMAR), was 0.10 ± 0.33 in group 1 and 0.26 ± 0.42 in group 2. The mean operation times for groups 1 and 2 were 11.2 ± 4.54 minutes and 7.00 ± 2.20 minutes, respectively (p=0.0024). Detachment of the IOL haptic from the optic during surgery occurred in four eyes in group 2 (16%), but did not occur in group 1. Iris capture of the optic was observed in 3 of the 13 eyes (23%) without a peripheral iridotomy in group 2. No peripheral iridotomies were performed on group-1 eyes, but iris capture did not occur in that group. Conclusions. There was a trend to fewer intraoperative and postoperative complications when using NX-70 IOLs. On the other hand, PN6A IOLs was easy to maneuver within the anterior chamber, and the operation time was shorter when using PN6A IOLs. Selection of optimal IOLs for flanged IOL fixation necessitates an understanding of their characteristics in terms of intraoperative and postoperative complications.